Sunday

March 29, 2015

March 29, 2015

Posted by **Nevin** on Monday, May 28, 2012 at 9:07pm.

- Calculus -
**Reiny**, Monday, May 28, 2012 at 10:04pmf'(x) = ( a(x^2 - 5x + 4) - (2x-5)(ax+b) )/(x^2 - 5x +4)^2

= 0 for a horizontal line

when x = 2

a(-2) + (2a+b) = 0

-2a + 2a + b = 0

b = 0

also f(2) = -1

2a/(4 - 10 + 4) = -1

2a/-2 = 1

a = 1

a=1 , b=0

so f(x) = x/(x^2 - 5x + 4)

**Answer this Question**

**Related Questions**

Calculus - 55. Find an equation of the tangent line to the graph of f(x) =x^3 - ...

Calculus - Given the function y=(x^2-5/x+3), answer the following questions. a) ...

Math- calculus - Given f(x) = x ^ 3 - x ^ 2 -4x +4 Find the zeros of f. Write an...

Calculus - 1. Given the function f defined by f(x) = x^3-x^2-4X+4 a. Find the ...

Calculus - Functions? - #1. A cubic polynomial function f is defined by f(x) = ...

Calculus - Suppose f(x)= e^(-1/x). Graph this function in the window -5(</=)x...

Calculus - Suppose f(x)= e^(-1/x). Graph this function in the window -5(</=)x...

Calculus - Let f be the function given by f(x)=(x^3)/4 - (x^2)/3 - x/2 + 3cosx. ...

calculus - 1. Which of the following expressions is the definition of the ...

calculus - 1. Which of the following expressions is the definition of the ...